Cipedak Avocado Cultivation as an Ecotourism Attraction in Betawi Setu Babakan Cultural Village - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Fitri, Novita Iza; Putra, Suadi Sapta (CV ODIS, 2023)
Setu Babakan Betawi Cultural Village located in South Jakarta is a tourism destination with communities developed by a culture that includes ideas and works both physical and non-physical that have tourism potential in the image of Betawi culture and Betawi community. This tourism destination has a role as a tourist area that attracts tourists to visit and generate income for the surrounding community as well as a Betawi cultural conservation area in DKI Jakarta. Avocado is a plant that can thrive in tropical regions such as Indonesia. Avocados are also rich in antioxidation and nutrients such as fat, which is 9.8 g / 100 g of fruit flesh (Afrianti, 2010). One of the avocado varieties that has recently begun to be popularly cultivated by the people of Indonesia is the cipedak avocado even though some people know it today as Avocado Miki. This research uses interview techniques that will later be used as a source of data